2014
DOI: 10.1002/bdd.1904
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the extent and variation of grapefruit juice–drug interactions from the pharmacokinetic profile in the absence of grapefruit juice

Abstract: The aim of this study was to develop a method for predicting the extent of grapefruit juice (GFJ)-drug interactions and their interindividual variations from the pharmacokinetic profile in the absence of GFJ. The pharmacokinetic profiles of 13 drugs after intravenous and oral administration were used to develop and validate the method. For each drug, the proportion absorbed into the intestine and the intestinal availability (Fg ) were calculated from clinical data taken from the literature. Then, the AUC ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is generally utilized to cure cardiovascular disorders, e.g., hypertension, chronic stable angina pectoris, and congestive heart failure. Nisoldipine is effective and presents less side effects. In addition, nisoldipine is used as a mild diuretic. , However, due to poor solubility in water, the bioavailability and first-pass metabolism of this drug are actually constrained. ,, To increase the poor solubility of drugs, numerous methodologies have been used in the literature, such as cosolvency, microemulsion, inclusion complex, solid dispersion, and surfactants. ,,, It is a common sense that cosolvency is a valuable solubilization approach employed to improve the equilibrium solubility magnitudes of poorly soluble drugs, ,, where an enormous number of exact solubility data are desired. Much attention has been given on the usages of this effective drug in existing investigations; however, there is little research on the solid–liquid equilibrium related to the drug dissolved in solvent systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally utilized to cure cardiovascular disorders, e.g., hypertension, chronic stable angina pectoris, and congestive heart failure. Nisoldipine is effective and presents less side effects. In addition, nisoldipine is used as a mild diuretic. , However, due to poor solubility in water, the bioavailability and first-pass metabolism of this drug are actually constrained. ,, To increase the poor solubility of drugs, numerous methodologies have been used in the literature, such as cosolvency, microemulsion, inclusion complex, solid dispersion, and surfactants. ,,, It is a common sense that cosolvency is a valuable solubilization approach employed to improve the equilibrium solubility magnitudes of poorly soluble drugs, ,, where an enormous number of exact solubility data are desired. Much attention has been given on the usages of this effective drug in existing investigations; however, there is little research on the solid–liquid equilibrium related to the drug dissolved in solvent systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nisoldipine is used as a mild diuretic. 23,24 However, due to poor solubility in water, the bioavailability and first-pass metabolism of this drug are actually constrained. 20,25,26 To increase the poor solubility of drugs, numerous methodologies have been used in the literature, such as cosolvency, microemulsion, inclusion complex, solid dispersion, and surfactants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The previous publication has reported that it cannot bring about symptomatic bradycardia or reflex tachycardia at therapeutic doses and has no obvious negative inotropic effect . In addition, nisoldipine exhibits a mild diuretic effect. , However, its bioavailability is very restricted due to its poor aqueous solubility and first-pass metabolism. ,, The pharmacokinetics and pharmacology of nisoldipine have been studied in detail but no attention has been paid on the solid–liquid equilibrium and solvent mixtures for improving the aqueous solubility to improve the bioavailability of nisoldipine. As is well known, co-solvent is an important means to improve the aqueous solubility of drugs; the knowledge of the solubility of drugs in solvents or solvents mixtures is vital for drugs dosage, bioavailability, curative effect, and chemical and physical stabilities of pharmaceutical dissolution …”
Section: Introductionmentioning
confidence: 99%